BIRDS-2: A Constellation of Joint Global Multi-Nation 1U CubeSats. (January 2019) - Azami, M H; Maeda, G.; Faure, P.; Yamauchi, T.; Kim, S.; Masui, H.; Cho, Mengu
Abstract: BIRDS-2, the second generation of the Joint Global Multi-Nation Birds (JGMNB) project is a constellation of 1U CubeSats from Laboratory of Spacecraft Environment Interaction Engineering (LaSEINE), Kyushu Institute of Technology, Japan. The BIRDS-2 project consists of three identical 1U built by a group of students from four nations; Japan, Malaysia, Philippines, and Bhutan. It consists of 6 missions; Camera, Automatic Radio Packet Service-Digipeater (APRS-DP), Store and Forward (S&F), COTS GPS, Anisotropic Magneto Resistance Magnetometer (AMR-MM), and detection of single-event latch-up (SEL). The objective of BIRDS-2 is to provide an opportunity to learn the entire satellite system cycle, to lay down the foundation of the sustainable space program, and to create international networks of the ground station to assist the infant space program of the participating country. A total of 11 members learns the satellite development in a lean concept of 30m radius of the work area. The paper will describe the bus system of the BIRDS-2 CubeSats and the development process throughout the one year and three months of the project timeline. Completion of BIRDS-2 flight models remarks the successful design of the CubeSats bus system and waiting for the launch and deploy from International Space Station (ISS) around 3 rd quarter of this year.